Estimation of biases and uncertainties on PWR nuclide inventories for severe accidents analyses - Ichou, R.; Clavel, J. B.; Bonthoux, S.; Bernard, F.; Taforeau, J.; Malvagi, F. (Frontiers in Energy Research, 2023)
The work presented in this paper deals with bias and uncertainty quantification on nuclear fuel inventories in a PWR core during normal operation. These actinides and fission products inventories are used as input data for radiological releases evaluation in case of a severe accident. The different sources of bias and uncertainty, as well as their impacts for UO2 and MOX fuel at the assembly and core levels, are discussed. Uncertainty sources include technological uncertainties (e.g. dimensions, irradiation history, temperatures), modeling assumptions, uncertainties related to the resolution methods used in the calculation tools and nuclear data uncertainties. For each source of uncertainty investigated in this paper, an evaluation of the associated biases and uncertainties on nuclide inventories is performed. It is shown that, among the sources of bias and uncertainties studied, spread due to nuclear data as well as the bias and uncertainties due to "infinite lattice approximation" are the most significant ones, for the isotopes of interest.